Impact of Dynamic Endoscopy and Bimanual-Binarial Dissection in Endoscopic Endonasal Surgery Training: A Laboratory Investigation - Vaz-Guimaraes, Francisco; Rastelli, Milton M., Jr; Fernandez-Miranda, Juan C.; Wang, Eric W.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2015)
Objective The lack of a standard technique may be a relevant issue in teaching endoscopic endonasal surgery (EES) to novice surgeons. The objective of this article is to compare different endoscope positioning and microsurgical dissection techniques in EES training.Methods A comparative trial was designed to evaluate three techniques: group A, one surgeon performing binarial two-hands dissection using an endoscope holder (rigid endoscopy); group B, two surgeons performing a combined binarial two- and three-handed dissection with one surgeon guiding the endoscope (dynamic endoscopy); and group C, two surgeons performing a binarial two-hands dissection with one surgeon dedicated to endoscope positioning and the other dedicated to a two-handed dissection. Trainees were randomly assigned to these groups and oriented to complete surgical tasks in a validated training model for EES. A global rating scale, and a specific-task checklist for EES were used to assess surgical skills.Results The mean scores of the global rating scale and the specific-task checklist were higher (p = 0.001 and 0.002, respectively) for group C, reflecting the positive impact of dynamic endoscopy and bimanual dissection on training performance.Conclusions We found that dynamic endoscopic and bimanual-binarial microdissection techniques had a significant positive impact on EES training.
Keywords: endoscopic endonasal surgery; surgical technique; surgical training; performance assessment